Using Digital Technologies in Response to the COVID-19 Pandemic in Portugal - Diana Portela; Duarte Vital Brito; Hugo Monteiro (Portuguese Journal of Public Health, 2022)
Digital technologies revolutionized the way we dealt with the COVID-19 pandemic and outstood the obvious societal change in the information age. Currently, data are an essential element of any health institution. Their use has the potential to radically reduce the cost and time needed to strengthen scientific evidence on the effectiveness of interventions. Likewise, information and the potential of these technologies have become a crucial part of the response to the pandemic. Effective implementation of data management strategies has depended on the adoption of digital technologies and their integration with health policies and care systems. In August 2020, Nature Medicine published an article about technological maturity and digital responses in the context of the COVID-19 pandemic. This paper aims to provide a contextualization of the technologies adopted in Portugal in the current crisis while highlighting, when applicable, requirements, potentials, constraints and aspects of possible improvements. The digital maturity of health services is a gradual process that requires preparation, adaptation and response. The future of public health and health care systems will be increasingly digital, and it is necessary to promote a culture of innovation, coordinate and standardize processes and make room for a new paradigm of sustainable digital transformation.